Resilient Elements Used by Students from Vasco de Quiroga Rural Normal School (Michoacán Mexico) in their Movement - Arreola Piñón, Cinthia Gricell (2021)
The aim of this paper is to describe the resilient resources that the students of Escuela Normal Rural Vasco de Quiroga, Michoacán, México use in their student/social movement and in their professional training. This research was carried out through a qualitative methodology, of the phenomenological kind, with the participation of 40 male students, using the focus group technique in 4 groups of 10 members each. The findings show the presence of such resilient elements as a positive attitude and the perception of personal growth and learning achievement from the student movement. This allows us to conclude that this type of movement generates positive aspects in students, which points to the importance of carrying out research emphasizing the knowledge of these phenomena not only as social or political movements but as promoters of psychological resources and human potential.